ANALISIS KONTRIBUSI PENDAPATAN USAHATANI CENGKEH TERHADAP PENDAPATAN RUMAH TANGGA TANI DI DESA DUNGINGIS KECAMATAN DAKO PEMEAN KABUPATEN TOLITOLI (STUDI KASUS PADA KELOMPOK TANI MEKAR 2) - Nurmala Nurmala; Narullah; Moh. Asse (Jurnal Agrotech, 2020)
This study aims to determine the amount of farm household income in clove farming and the contribution of clove farming to total farm household income in Mekar 2 Farmer Group in Dungingis Village, Dako Pemean Subdistrict, Tolitoli Regency. This research was conducted from July to September 2018. The research method used was the census method with a sample of 20 respondents. The results of this study indicate that clove farming income is the source of income that contributes the most from all sources of income of farm families, amounting to Rp.579,277,557 per year or 56.44%.